Tourism and hospitality research on Iran: current state and perspectives. Issue 1 (1st January 2019) - Seyfi, Siamak; Hall, C. Michael; Kuhzady, Salar
ABSTRACT: The tourism industry in Iran has grown rapidly following the relaxation of sanctions in the wake of the recent landmark nuclear agreement known as the Joint Comprehensive Plan of Action (JCPOA). However, despite the significance of tourism in the country, no study has previously provided an examination of research trends of tourism and hospitality studies on Iran. This review provides an overview of 180 papers identified in academic and bibliometric databases between 2000 and 2016. Through content analysis, the empirical findings indicate that the number of publications is continuously increasing since the nuclear accord, and the dominant research themes/foci identified among the Iranian tourism research community are tourism development followed by tourism marketing and ecotourism. The majority of the articles used empirical techniques and there is a tendency toward multiple-authorship. The history and scope of sanctions on Iran since the establishment of the theocratic Islamic Republic of 1979 and its consequences on the scientific research are also explained. Implications for the further development of tourism and hospitality research in Iran particularly in the light of softening of sanctions are also discussed.